Response Surface Methodology - Research Advances and Applications 2023
DOI: 10.5772/intechopen.105899
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Baker’s Yeast Production on Grape Juice Using Response Surface Methodology

Abstract: The purpose of this study is to complete as an example the fermentation conditions allowing the production of Saccharomyces cerevisiae yeast biomass in large quantities using the juice as the same carbon source. Determination of the best of five factors affects the production of dry biomass by baker’s yeast. The optimal value of the five factors affecting the process of biomass production by the baker’s sourdough was determined. The experimental design was performed using CCD (Central Composite Experimental De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Mahmood et al . ( 35 ) reported the maximum growth of yeast biomass of 41 g/L. In addition, Lo Curto et al ( 36 ) reported that the yields of baker’s yeast on grape marc were lower than those obtained in industrial production.…”
Section: Resultsmentioning
confidence: 99%
“…Mahmood et al . ( 35 ) reported the maximum growth of yeast biomass of 41 g/L. In addition, Lo Curto et al ( 36 ) reported that the yields of baker’s yeast on grape marc were lower than those obtained in industrial production.…”
Section: Resultsmentioning
confidence: 99%